Brain interstitial pH changes in the subacute phase of hypoxic-ischemic encephalopathy in newborn pigs - Remzső, Gábor (PLoS One, 2020)
Brain interstitial pH (pH(brain)) alterations play an important role in the mechanisms of neuronal injury in neonatal hypoxic-ischemic encephalopathy (HIE) induced by perinatal asphyxia. The newborn pig is an established large animal model to study HIE, however, only limited information on pH(brain) alterations is available in this species and it is restricted to experimental perinatal asphyxia (PA) and the immediate reventilation. Therefore, we sought to determine pH(brain) over the first 24h of HIE development in piglets. Anaesthetized, ventilated newborn pigs (n = 16) were instrumented to control major physiological parameters. pH(brain) was determined in the parietal cortex using a pH-selective microelectrode. PA was induced by ventilation with a gas mixture containing 6%O(2)-20%CO(2) for 20 min, followed by reventilation with air for 24h, then the brains were processed for histopathology assessment. The core temperature was maintained unchanged during PA (38.4±0.1 vs 38.3±0.1°C, at baseline versus the end of PA, respectively; mean±SEM). In the arterial blood, PA resulted in severe hypoxia (P(a)O(2): 65±4 vs 23±1*mmHg, *p<0.05) as well as acidosis (pH(a): 7.53±0.03 vs 6.79±0.02*) that is consistent with the observed hypercapnia (P(a)CO(2): 37±3 vs 160±6*mmHg) and lactacidemia (1.6±0.3 vs 10.3±0.7*mmol/L). Meanwhile, pH(brain) decreased progressively from 7.21±0.03 to 5.94±0.11*. Reventilation restored pH(a), blood gases and metabolites within 4 hours except for P(a)CO(2) that remained slightly elevated. pH(brain) returned to 7.0 in 29.4±5.5 min and then recovered to its baseline level without showing secondary alterations during the 24 h observation period. Neuropathological assessment also confirmed neuronal injury. In conclusion, in spite of the severe acidosis and alterations in blood gases during experimental PA, pH(brain) recovered rapidly and notably, there was no post-asphyxia hypocapnia that is commonly observed in many HIE babies. Thus, the neuronal injury in our piglet model is not associated with abnormal pH(brain) or low P(a)CO(2) over the first 24 h after PA.